Doubt m-Polar Fuzzy Sets Based on BCK-Algebras - Bayan Albishry; Sarah O. Alshehri; Nasr Zeyada (International Journal of Analysis and Applications, 2023)
Doubt m-polar subalgebras (ideals) were introduced and some properties were investigated. Also, doubt m-polar positive implicative (commutative) ideals were defined and related results were proved.